أثر تكنولوجيا المعلومات في جودة الخدمة المصرفية دراسة ميدانية على فروع المصرف التجاري السوري باللاذقية - قاسم, سامر (Latakia University Journal - Economic and Legal Sciences Series, 2016)
يهدف البحث إلى دراسة أثر تكنولوجيا المعلومات على جودة الخدمة المصرفية في فروع المصرف التجاري السوري بمحافظة اللاذقية, ولتحقيق أهداف البحث تمّ تطوير استبانة وتوزيعها على (201) عامل, وأعيد منها (183) استبانة, بنسبة استجابة بلغت (91.04%), وبالاعتماد على تحليل الانحدار البسيط تمّ دراسة العلاقة بين أبعاد تكنولوجيا المعلومات وجودة الخدمة المصرفية, وتوصل البحث للنتائج الآتية:1- هناك علاقة ارتباط قوية وموجبة بين بعد الأجهزة المعدات وجودة الخدمة المصرفية, حيث تبين أنّ (79.7%) من التباين الحاصل في جودة الخدمات المصرفية يفسره بعد الأجهزة والمعدات.2- هناك علاقة ارتباط قوية وموجبة بين بعد الانترنت وجودة الخدمة المصرفية, حيث تبين أنّ (69.2%) من التباين الحاصل في جودة الخدمات المصرفية يفسره بعد الانترنت.3- هناك علاقة ارتباط قوية وموجبة بين بعد الاتصالات وجودة الخدمة المصرفية, حيث تبين أنّ (65.9%) من التباين الحاصل في جودة الخدمات المصرفية يفسره بعد الاتصالات.4- هناك علاقة ارتباط مقبولة وموجبة بين بعد كفاءة الموارد البشرية وجودة الخدمة المصرفية, حيث تبين أنّ (59.9%) من التباين الحاصل في جودة الخدمات المصرفية يفسره كفاءة الموارد البشرية.The research aims to study the impact of information technology on the quality of banking services in the branches of the Commercial Bank of Syria province of Latakia. To achieve the objectives of the research, a questionnaire was developed and distributed to 201 workers, and (183) questionnaire were suitable to analyze, a response rate (91.04%), and based on applying simple regression to assess the relationship between the information technology and the quality of banking service dimensions, the research found the following results:1- There is a strong and positive correlation between the hardware equipment and the quality of banking service, where it was found that (79.7%) of the discrepancy in the quality of banking services is explained after the equipment.2- There is a strong and positive correlation between a online banking service and service quality, it was found that (69.2%) of the discrepancy in the quality of banking services is explained after the Internet.3- There is a strong and positive correlation between communications and banking service quality, where it was found that (65.9%) of the discrepancy in the quality of banking services is explained after the communication.4- There are acceptable and positive correlation between post-efficiency of human resources and banking service quality, where it was found that (59.9%) of the discrepancy in the quality of banking services is explained by the efficiency of human resources.